Аbsorption of diffuse light by 2D arrays of spherical particles. (October 2022) - Loiko, N.A.; Miskevich, A.A.; Loiko, V.A.
Highlights: Ordered array of Ag particles can absorb almost 10 times higher of light than partially ordered one. Light absorption by array under diffuse and directional illumination can differ more than two times for equal opening and incidence angles. Absorption at directional oblique illumination can be almost 10 times greater than under normal illumination. The developed approach allows one to optimize solar cells for various lighting conditions. Abstract: The problem of absorption of diffuse light by a 2D array of identical spherical particles is considered. The equations to solve this problem are derived on the basis of statistical approach. They can be used to match parameters of the array and the illumination system to get maximum absorption. The numerical results are presented for absorption coefficients of arrays with the imperfect triangular lattice and partially ordered structures of crystalline silicon and silver particles embedded in nonabsorbing medium, in the wavelength range 0.35 μm – 0.80 μm. The size of particles and their concentration are chosen so as to illustrate the dependence of light absorption on the angle of incidence under conditions of resonances due to the high spatial ordering of particles. The absorption coefficients of the arrays at diffuse and directional light illumination are compared.